2015
DOI: 10.5194/hess-19-1107-2015
|View full text |Cite
|
Sign up to set email alerts
|

A groundwater recharge perspective on locating tree plantations within low-rainfall catchments to limit water resource losses

Abstract: Abstract.Despite the many studies that consider the impacts of plantation forestry on groundwater recharge, and others that explore the spatial heterogeneity of recharge in low-rainfall regions, there is little marriage of the two subjects in forestry management guidelines and legislation. Here we carry out an in-depth analysis of the impact of reforestation on groundwater recharge in a low-rainfall (< 700 mm annually), high-evapotranspiration paired catchment characterized by ephemeral streams. Water table fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
0
33
0
3
Order By: Relevance
“…Other studies have shown similar dynamics of water‐table depth in Eucalyptus plantations as compared to our measurements and simulations (Manzione, Tanikawa & Soldera ; Dean et al . ; Smethurst, Almeida & Loos ). During the second stage of growth following canopy closure, we show that tree water uptake also comes from the capillary fringe, and therefore, the saturated zone acts as another buffering pool of water, being filled the first 2 years after clear‐cutting the previous stand and partly used after canopy closure.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown similar dynamics of water‐table depth in Eucalyptus plantations as compared to our measurements and simulations (Manzione, Tanikawa & Soldera ; Dean et al . ; Smethurst, Almeida & Loos ). During the second stage of growth following canopy closure, we show that tree water uptake also comes from the capillary fringe, and therefore, the saturated zone acts as another buffering pool of water, being filled the first 2 years after clear‐cutting the previous stand and partly used after canopy closure.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize the need for field data to properly quantify the potential effects of long-term pumping on forest conditions. Furthermore, a change in the species composition alters the vulnerability to drought and the relative magnitude of water balance components through changes in ET, both in terms of interception and transpiration [32,33,64]. For example, transpiration rates for a given diameter yellow poplar (Liriodendron tulipifera; diffuse porous xylem) were nearly twofold greater than for hickory (Carya spp.…”
Section: Groundwater Extractionmentioning
confidence: 99%
“…Some cases in point are studies of the water table response in three locations in the coastal plain region [26,39], and data have indicated that the specific yield of the surficial aquifer sediments was 0.1 or less, such that 5 mm of water loss by evapotranspiration (ET) can cause the water table depth to drop by at least 5 cm [40][41][42]. A comparable study in a drier climate, that used water table hydrograph data to understand groundwater recharge, found that the management of eucalypt stands in Australia can affect the water balance, but that the landscape position in that region was more important [32,33]. Many tectonically-passive coastal regions like the southern and southeastern U.S. face widespread impacts of water imbalances because of the generally flat topography.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations